UI/UX Design of GoHealth Mobile Application Using Design Thinking Approach - Al Fata, Umar; Mauladi, Teguh Ade; Fikri, Muhamad; Huda, Miftahul (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
The swift pace of digital change in healthcare has opened new doors for mobile health services (m-health), but users in developing areas still face major hurdles, like high consultation costs, no real-time updates on health facility activities, and poor usability of current platforms. This study wants to create a user-focused mobile health app,